Factors Affecting Implementation of Family Planning (FP) Work for the District of Sutera Nagari Amping Parak Pesisir Selatan District - -, Irfan - (STKIP PGRI Sumbar, 2014)
The problems discussed in this Research is the type of livelihood, income level, educationlevel, health, government socialization affect implementation of Family Planning (FP) in villageAmping Parak Sutera District of Pesisir Selatan District. The purpose of this research is theinfluence of education level, income level, health and education levels together towardsimplementation of Family Planning (FP). This type of research Descriptive research Correlationalclassified. The population of 420 families who carry out family planning programs in villageAmping Parak Kecematan Sutera, with samples taken 18% of the 75 persons. Data were collectedsecondary data and primary data and sourced from Statistics Office, wali village and relevantagencies. Data collection and research techniques used, recording and education angket. Theresults of the research show an effect on the implementation of the family planning program forthe People village Amping Parak Sutera District of District of 2658, the income effect on theimplementation of family planning programs for 2406, the health impact of the implementation offamily planning programs for 3007. Education, Income and Health jointly related to theimplementation of family planning programs for9042.